Live demonstration: a public engagement platform for invasive neural interfaces - Cavuto,M; Hallam,R; Rapeaux,A; Maslik,M; Troiani,F; Constandinou,T (IEEE, 2019)
Neural interfaces, and more specifically ones ofthe invasive/implantable variety, today are a topic of muchcontroversy, often making the general public uncomfortable andintimidated. We have thus devised a bespoke interactive demoto help people understand brain implants and their need inthe age of wearable devices, with the secondary objective ofintroducing the wireless cortical neural probe that we, at NGNI(Next Generation Neural Interfaces) lab, are developing.